Homeostatic antiviral protection of the neonatal gut epithelium by interferon lambda - Bryan Ramirez Reyes; Shelby Madden; Kimberly A. Meyer; Brenden Bartsch; Austin P. Wright; David A. Constant; Timothy J. Nice (Cell Reports)
Summary: Cell-intrinsic antiviral gene expression by intestinal epithelial cells (IECs) limits infection by enteric viral pathogens. Here, we find that neonatal IECs express antiviral genes at homeostasis that depend on interferon lambda (IFN-λ) and are required for early control of mouse rotavirus (mRV) infection. Neonatal homeostatic IFN-λ responses are independent of microbiota and pervasively distributed among IECs, distinguishing them from the homeostatic responses of adult mice. Developmental differences in homeostatic IFN-stimulated gene signatures of the intestine are regulated by maturation during the suckling-to-weanling transition, which includes reduced expression of Prdm1 by mature IECs. These studies identify developmental regulation of the homeostatic IFN-λ response, which is present in the neonatal intestine from birth, stimulated independent of microbiota, and preemptively protects IECs from viral infection. This intrinsically programmed antiviral response in early life is particularly important due to the absence of a robust microbiota or protective immune memory at birth, when the risk of enteric infection is high.